A chromosome-level genome reveals genome evolution and molecular basis of anthraquinone biosynthesis in Rheum palmatum - Tianyi Zhang; Lipan Zhou; Yang Pu; Yadi Tang; Jie Liu; Li Yang; Tao Zhou; Li Feng; Xumei Wang (BMC Plant Biology, 2024)
Abstract Background Rhubarb is one of common traditional Chinese medicine with a diverse array of therapeutic efficacies. Despite its widespread use, molecular research into rhubarb remains limited, constraining our comprehension of the geoherbalism. Results We assembled the genome of Rheum palmatum L., one of the source plants of rhubarb, to elucidate its genome evolution and unpack the biosynthetic pathways of its bioactive compounds using a combination of PacBio HiFi, Oxford Nanopore, Illumina, and Hi-C scaffolding approaches. Around 2.8 Gb genome was obtained after assembly with more than 99.9% sequences anchored to 11 pseudochromosomes (scaffold N50 = 259.19 Mb). Transposable elements (TE) with a continuous expansion of long terminal repeat retrotransposons (LTRs) is predominant in genome size, contributing to the genome expansion of R. palmatum. Totally 30,480 genes were predicted to be protein-coding genes with 473 significantly expanded gene families enriched in diverse pathways associated with high-altitude adaptation for this species. Two successive rounds of whole genome duplication event (WGD) shared by Fagopyrum tataricum and R. palmatum were confirmed. We also identified 54 genes involved in anthraquinone biosynthesis and other 97 genes entangled in flavonoid biosynthesis. Notably, RpALS emerged as a compelling candidate gene for the octaketide biosynthesis after the key residual screening. Conclusion Overall, our findings offer not only an enhanced understanding of this remarkable medicinal plant but also pave the way for future innovations in its genetic breeding, molecular design, and functional genomic studies.